HDAC superfamily promoters acetylation is differentially regulated by modafinil and methamphetamine in the mouse medial prefrontal cortex. (27th February 2019) - González, Betina; Bernardi, Alejandra; Torres, Oscar V.; Jayanthi, Subramaniam; Gomez, Natalia; Sosa, Máximo H.; García‐Rill, Edgar; Urbano, Francisco J.; Cadet, Jean‐Lud; Bisagno, Verónica
Abstract: Dysregulation of histone deacetylases (HDAC) has been proposed as a potential contributor to aberrant transcriptional profiles that can lead to changes in cognitive functions. It is known that METH negatively impacts the prefrontal cortex (PFC) leading to cognitive decline and addiction whereas modafinil enhances cognition and has a low abuse liability. We investigated if modafinil (90 mg/kg) and methamphetmine (METH) (1 mg/kg) may differentially influence the acetylation status of histones 3 and 4 (H3ac and H4ac) at proximal promoters of class I, II, III, and IV HDACs. We found that METH produced broader acetylation effects in comparison with modafinil in the medial PFC. For single dose, METH affected H4ac by increasing its acetylation at class I Hdac1 and class IIb Hdac10, decreasing it at class IIa Hdac4 and Hdac5 . Modafinil increased H3ac and decreased H4ac of Hdac7 . For mRNA, single‐dose METH increased Hdac4 and modafinil increased Hdac7 expression. For repeated treatments (4 d after daily injections over 7 d), we found specific effects only for METH. We found that METH increased H4ac in class IIa Hdac4 and Hdac5 and decreased H3/H4ac at class I Hdac1, Hdac2, and Hdac8 . At the mRNA level, repeated METH increased Hdac4 and decreased Hdac2 . Class III and IV HDACs were only responsive to repeated treatments, where METH affected the H3/H4ac status of Sirt2, Sirt3, Sirt7, and Hdac11 . Our results suggest that HDAC targets linked to the effects of modafinil and METH may be related to the cognitive‐enhancing vs cognitive‐impairing effects of these psychostimulants. Abstract : Modafinil and METH treatment induced common and differential histones 3 and 4 acetylation profiles on HDACs family promoters in the mPFC. The Venn diagrams depict the specific and overlapped HDAC promoters with altered acetylation status, identified after single‐dose and repeated injections of modafinil (gray) and METH (black). First diagram on the left for each time point correspond to H3ac, second diagram correspond to H4ac. In red: increased acetylation, in blue: decreased acetylation, compared to vehicle‐treated controls.